2015
DOI: 10.1016/j.mcn.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic and therapeutic implications for the cell biology of parkin

Abstract: Mutations in the E3 ligase parkin are the most common cause of autosomal recessive Parkinson's disease (PD), but it is believed that parkin dysfunction may also contribute to idiopathic PD. Since its discovery, parkin has been implicated in supporting multiple neuroprotective pathways, many revolving around the maintenance of mitochondrial health quality control and governance of cell survival. Recent advances across the structure, biochemistry, and cell biology of parkin have provided great insights into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 175 publications
(229 reference statements)
0
25
1
Order By: Relevance
“…66,67 These discordances may be explained by considering that interaction of the mitochondrial mutation pattern with mtQC-mitophagy is a complex process dependent on multiple factors, such as cell bioenergetics, culture conditions, level of PARK2 expression, cell-type and specific mtDNA mutations. 68 Of note, our data were obtained in cells containing the same mutation and were grown in identical culture conditions therefore minimizing the factors that strongly influence bioenergetic status, morphology and dynamics of mitochondria. 28,69 Therefore, the differences observed in mtQC and bioenergetics are due to the respective cell-type specificity.…”
Section: Discussionmentioning
confidence: 99%
“…66,67 These discordances may be explained by considering that interaction of the mitochondrial mutation pattern with mtQC-mitophagy is a complex process dependent on multiple factors, such as cell bioenergetics, culture conditions, level of PARK2 expression, cell-type and specific mtDNA mutations. 68 Of note, our data were obtained in cells containing the same mutation and were grown in identical culture conditions therefore minimizing the factors that strongly influence bioenergetic status, morphology and dynamics of mitochondria. 28,69 Therefore, the differences observed in mtQC and bioenergetics are due to the respective cell-type specificity.…”
Section: Discussionmentioning
confidence: 99%
“…As a ubiquitously expressed E3 ligase, parkin has been shown to be involved in the UPS, and studies in parkin overexpression have confirmed enhanced proteasome activity (Khandelwal, 2010). Screening for parkin substrates has identified hundreds of proteins, including proteins involved in the epidermal growth factor pathway, Wnt signaling, inflammation, mitochondrial homeostasis, Lewy body formation, and apoptosis, suggesting broad involvement of parkin ubiquitination (Charan and LaVoie, 2015; von Coelln et al, 2004). Lack of parkin activity would suggest an accumulation of its substrates, leading to aberrant cell signaling and neurotoxicity.…”
Section: Common Pathways In Pd Pathogenesismentioning
confidence: 99%
“…Parkin’s neuroprotective role has been extensively observed in a variety of oxidative stress conditions, including mitochondrial, ER, proteolytic, and dopamine stress (Charan and LaVoie, 2015). Though parkin’s primary function in mediating oxidative stress appears to be in regulating mitophagy, it has been implicated in other pro-survival roles.…”
Section: Common Pathways In Pd Pathogenesismentioning
confidence: 99%
See 2 more Smart Citations